Study of Raw Materials for Manufacturing Perforated Clay Bricks (Chamchamal, and Qaradagh Regions in Sulaimani / Iraq) - Rashed, Kamal Ahmad (Sulaimani Journal for Engineering Sciences, 2017)
There is no information about the optimum molding moisture content and molding pressure on the physical and mechanical properties of clay bricks. In this paper, the effect of moisture content and applied pressure during molding of brick samples for two selected locations of Sulaimani province in Iraq were studied. After firing the molded brick samples at a temperature of 1000oC, the physical and mechanical properties were studied from the following tests: firing shrinkage, water absorption, dry density and uniaxial compressive strength. The results indicate that the optimum moisture content for molding and manufacturing of clay bricks is within (0.6 to 0.7) of plastic limit of the raw materials. Also, it was found that the sufficient applied pressure during molding of clay bricks is 6 MPa.
Keywords: Perforated clay bricks; Density; Compression strength; Water absorption; Fired shrinkage; Chamchamal; Qaradagh